Slow hydrolysis of amylose in soluble starch and amylopectin in suspendable starch liberated from non-glutinous rice flour heated with a sorghum extract - Umeo Takahama; Toshihiro Ansai; Sachiko Hirota (Heliyon, 2022)
Polyphenols in plant can interact with amylose and amylopectin in different ways affecting their hydrolysis by α-amylase. Pancreatin liberated starch from non-glutinous rice flour heated with and without an aqueous extract of sorghum seeds, and hydrolyzed the liberated starch. The hydrolysis of the liberated starch was slowed down by the sorghum extract. Then, the liberated starch was fractionated into soluble starch and suspendable starch. In the soluble starch, amylose hydrolysis was slowed down more significantly than amylopectin hydrolysis, and in the suspendable starch, the hydrolysis of amylopectin was slowed down efficiently by the sorghum extract. It is discussed that (i) the slowdown in the former might be due to the binding of sorghum components including procyanidins to amylose, and that (ii) the slowdown in the latter might be due to the complex formation between amylopectin and shorter amylose combined with the sorghum components. The contribution of amylose to the slowdown was supported by the result that the sorghum extract inhibited the starch hydrolysis only slightly in glutinous rice flour, the starch of which was almost composed of amylopectin. It was proposed a possible mechanism of the slowdown of amylopectin hydrolysis in suspendable starch by shorter amylose combined with the sorghum components.